Frequent Interpersonal Stress and Inflammatory Reactivity Predict Depressive-Symptom Increases: Two Tests of the Social-Signal-Transduction Theory of Depression - Madison, Annelise A.; Andridge, Rebecca; Shrout, M. Rosie; Renna, Megan E.; Bennett, Jeanette M.; Jaremka, Lisa M.; Fagundes, Christopher P.; Belury, Martha A.; Malarkey, William B.; Kiecolt-Glaser, Janice K. (Psychological Science, 2022)
The social-signal-transduction theory of depression asserts that people who experience ongoing interpersonal stressors and mount a greater inflammatory response to social stress are at higher risk for depression. The current study tested this theory in two adult samples. In Study 1, physically healthy adults ( N = 76) who reported more frequent interpersonal tension had heightened depressive symptoms at Visit 2, but only if they had greater inflammatory reactivity to a marital conflict at Visit 1. Similarly, in Study 2, depressive symptoms increased among lonelier and less socially supported breast-cancer survivors ( N = 79). This effect was most pronounced among participants with higher inflammatory reactivity to a social-evaluative stressor at Visit 1. In both studies, noninterpersonal stress did not interact with inflammatory reactivity to predict later depressive symptoms.